2015
DOI: 10.1530/joe-14-0571
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine decreases IGFBP1 production in db/db mice through suppression of HIF-1

Abstract: IGF binding protein 1 (IGFBP1) is a member of the binding proteins for the IGF with an important role in glucose homeostasis. Circulating IGFBP1 is derived essentially from the liver where it is mainly regulated negatively by insulin. Carnosine, a natural antioxidant, has been shown to improve metabolic control in different animal models of diabetes but its mechanisms of action are still not completely unraveled. We therefore investigate the effect of carnosine treatment on the IGFBP1 regulation in db/db mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
1
21
0
1
Order By: Relevance
“…CD248 expression was knocked down by RNAi in human in vitro differentiated adipocytes at day 10 of differentiation using 40 nM siRNA oligonucleotides (M-010720-00-0005, Dharmacon) and compared with non-silencing control RNAi (D-001206-13-05). The electroporation of siRNA was combined with 1 μg of plasmids containing the hypoxia response element (HRE) (previously described in [24]) coupled to a luciferase reporter and 0.1 μg Renilla. Cells were electroporated at day 10 of differentiation as previously described [19] and were then incubated in a hypoxic chamber at day 12 and harvested for subsequent analysis at day 13.…”
Section: Methodsmentioning
confidence: 99%
“…CD248 expression was knocked down by RNAi in human in vitro differentiated adipocytes at day 10 of differentiation using 40 nM siRNA oligonucleotides (M-010720-00-0005, Dharmacon) and compared with non-silencing control RNAi (D-001206-13-05). The electroporation of siRNA was combined with 1 μg of plasmids containing the hypoxia response element (HRE) (previously described in [24]) coupled to a luciferase reporter and 0.1 μg Renilla. Cells were electroporated at day 10 of differentiation as previously described [19] and were then incubated in a hypoxic chamber at day 12 and harvested for subsequent analysis at day 13.…”
Section: Methodsmentioning
confidence: 99%
“…Development of carnosine derivatives resistant to CN1 hydrolysis has become the subject of emerging interest in recent years 20 . In rodents, no serum CN1 is present and carnosine supplementation of diabetic mice increases serum and tissue carnosine levels and mitigates DN, reduces renal vasculopathy 21 , normalizes vascular permeability 21 , improves wound healing 22 and decreases insulin growth factor binding protein-1 (IGFBP1) production through suppression of HIF-1α, and improves glucose homeostasis 23 . Moreover, in streptozotocin-induced diabetic rats, carnosine prevents apoptosis of glomerular cells, podocyte loss 24 , 25 , and vascular damage 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a protective role for carnosine has also been reported in diabetes [66,67]. Indeed, carnosine concentrations in the livers of diabetic mice are lower than those in control mice [68]. In this same study, carnosine was reported to decrease the circulating insulin-like growth factor-binding protein (IGFBP) levels, through a mechanism that involved the suppression of HIF-1α-mediated IGFBP induction [68].…”
Section: Carnosine and Histidine-iron(ii) Chelators Of Physiological mentioning
confidence: 70%